Administração discursiva - (:unkn) unknown (SALUTE, 2019)
The research on discursive administration gathered in the collection that the reader has in hand develops against this background in which stands out the emergence of a society of communication and information in response to disruptions and technological impacts. They start from the observation that current models of management based exclusively on the systemic model can no longer cover the demands of training and information. This is because the communication and participation between managers and teams, between the libraries and their members is incipient. It is interesting to note that the texts are not confined to describing or regretting the new scenarios; instead, they concentrate on formulating interesting proposals to address the new challenges that arise in the area of ​​administration in general and libraries in particular. They result from the conviction that in the disruptive threats that accompany the present era of transformations are embedded new opportunities to be harnessed by creating a communicative and discursive, innovative and open environment.
Keywords: Ciência da informação; Administração discursiva; Habermas; Novas tecnologias; Comunicação; Política; CNPQ::CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO